Choledochoduodenostomy in the treatment of cholangitis - Viola Núñez, Humberto; Antúnez, Carlos; Costa di Fabio, José M; Ramírez, Wilson (Cirugía del Uruguay, 1983)
In 13 patients operated on, they analyze the symptomatology and expose the technique of the side to side C-D and the conditions for performing it